COMPARATIVE IN- VITRO EVALUATION OF VANCOMYCIN MINIMUM INHIBITORY CONCENTRATIONBY AGAR DILUTION AND E-STRIP IN METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - Sheroze Ilyas (Army Medical College Rawalpindi, 2021)
Objective: To compare the in-vitro efficacy by determining Minimum Inhibitory Concentration of Vancomycin using the reference Agar Dilution to the E-Strip in Methicillin Resistant Staphylococcus aureus isolates.